Seroprevalence of Hepatitis B Infection among Pregnant Women in Southern Odisha - Neha Samal; Sanghamitra Padhi; Laxmi Burman (Indian Journal of Medical Specialities)
Background: Hepatitis B virus (HBV) infection continues to be a life- threatening health problem throughout world, infecting more than two billion people. While blood transfusion and unsafe therapeutic injection continue to be major risk factors, the role of vertical transmission remains under- estimated. Hence, this study was done to find out the prevalence of HBV infection and associated risk factors among healthy pregnant ladies in Southern Odisha. The present study was a prospective, observational study conducted, in the department of Microbiology, with collaboration of department of Obstetrics and Gynecology of MKCG Medical college from 1st March 2017 to 28th Feb 2018. Methodology: After collection of three to four millilitre of venous blood from the clients, sera was separated by centrifugation. They were then tested for Hepatitis B surface antigen (HBsAg) by Enzyme linked Immunsorbent assay (ELISA). Serological status of the subjects and correlation with their socio-economic characteristic was noted using a preset proforma. Babies born to HBsAg positive ladies were administered Hepatitis B vaccine and immunoglobulin. Results: Total 3,230 in non-duplicating serum samples were screened among which 150 (4.64%) were tested positive for HBsAg. Ladies with multiple sexual partners (57. 14%) followed by intravenous drug users (7.88%) were mostly positive for HBsAg. Conclusion: Exposure to risky social behavioural pattern, lack of awareness could be suggested as possible means of acquiring the infection. Immunization is the most effective and only way of preventing development of chronic carrier state. Hence all neonates were administered with hepatitis B vaccine and 0.5 ml of hepatitis B immunoglobulin within 12 hours of birth.